A blue revolution in sub-Saharan Africa? Evidence from Ghana’s tilapia value chain - Ragasa, Catherine; Andam, Kwaw S.; Kufoalor, Doreen S.; Amewu, Sena (International Food Policy Research Institute, 2018)
Global growth in aquaculture is underway – a “blue revolution” featuring rapid increases in demand for fish and a corresponding surge in aquaculture production. This paper describes the fast-growing tilapia value chain in Ghana to demonstrate the features of a nascent blue revolution in sub-Saharan Africa (SSA) and to illustrate its potential for job creation and reducing poverty and food insecurity there. Tilapia production has been growing at 15 percent annually in SSA, but imports are also surging to satisfy the growing appetite for tilapia. This paper illustrates how aquaculture can grow sustainably in SSA within the context of growing demand and global competition. A value chain analysis is conducted using secondary data analysis, desk reviews of experiences and lessons from other countries, interviews with 95 actors in the tilapia value chain in Ghana, and detailed production and profitability data from Ghanaian tilapia farmers. A profitable farmed tilapia industry has been established in Ghana with the potential to expand supply to satisfy local demand and to export to neighboring countries. Productivity in the industry has grown mainly through reducing the mortality rates of fingerlings and improvements in the supply of locally-produced high-quality fish feed. Feed costs remain high. However, there is potential to reduce those costs by improving the productivity of crops that are used in fish feed, particularly maize and soybean. Reducing local feed costs will have positive spillover effects on both other pond-based aquaculture systems and on the livestock feed sector. Moreover, Ghana can expand it fish feed production to be an important source of feed within SSA. The industry can further increase aquaculture productivity through the adoption of faster-growing fish strains and better management practices. Ghana’s aquaculture sector could grow even faster by adopting lessons from other countries, including on infrastructure provision, fiscal incentives for the production of fish feed ingredients, and sustainable fish farming practices, particularly through paying close attention to water and feed quality and addressing food safety concerns within the sector.